Implementasi Kebijakan Pengelolaan Sampah Berbasis Sumber Dalam Keberlajutan Daerah Aliran Sungai (DAS) Ayung - Pande Made Ari Ananta Paramarta; Sang Ayu Made Ary Kusumawardhani (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the sustainability of the Ayung Watershed (DAS Ayung) across ecological, economic, social, and political dimensions and to evaluate the influence of Bali Governor Regulation No. 47 of 2019 on watershed sustainability. The research was conducted in the upstream, middle, and downstream areas of the Ayung Watershed from June to December 2025 using primary and secondary data. Multidimensional Scaling (MDS) was applied to assess sustainability levels, while Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to examine the regulation’s impact. The MDS results indicate an overall sustainability index of 62.76, classified as moderately sustainable. The social dimension achieved the highest score (70.12), while the economic dimension showed the lowest (55.80). The PLS-SEM analysis revealed that waste management, forest conservation, community education, and regulatory supervision significantly affect watershed sustainability, whereas sustainable infrastructure development does not show a significant effect. These findings demonstrate that the implementation of Bali Governor Regulation No. 47 of 2019 strengthens watershed management through integrated ecological and institutional governance. The study suggests improving regulatory enforcement, enhancing community environmental education, and fostering intersectoral collaboration. The implications highlight the necessity for coordinated policy actions to maintain the ecological balance and long-term sustainability of the Ayung Watershed as a key natural and economic resource for Bali’s sustainable development.